2013
DOI: 10.1055/s-0033-1343950
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Low Molecular Weight Dextran (Dextran 40) in Head and Neck Free Flap Reconstruction

Abstract: Though dextran 40 did not result in any significant adverse local or systemic complications, it is not useful as a postoperative antithrombotic agent in head and neck oncologic reconstruction with free tissue transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 23 publications
0
38
0
Order By: Relevance
“…Among previous studies that have specifically compared different antithrombotic agents regarding haematoma and thrombosis in free flap surgery [4,[6][7][8][9][10][11][12] (Table 5), only one prospective randomised study could be identified [10]. In accordance with the study by Disa et al [10], where they evaluated the use of dextran in 100 head and neck free flap cases, we omitted peri-and postoperative dextran from our treatment protocol in 2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among previous studies that have specifically compared different antithrombotic agents regarding haematoma and thrombosis in free flap surgery [4,[6][7][8][9][10][11][12] (Table 5), only one prospective randomised study could be identified [10]. In accordance with the study by Disa et al [10], where they evaluated the use of dextran in 100 head and neck free flap cases, we omitted peri-and postoperative dextran from our treatment protocol in 2011.…”
Section: Discussionmentioning
confidence: 99%
“…dextran). Several animal studies have demonstrated favourable effects on free flap outcome by these different agents, whereas clinical studies have failed to reproduce these results in humans [4,[6][7][8][9][10][11][12]. Although most agents are used to prevent systemic thrombosis today, many centres still use different agents to improve the flap outcome [4,13].…”
Section: Introductionmentioning
confidence: 99%
“…The remaining 19 studies were retrospective cohort studies. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] Study characteristics are summarized in Table 2.…”
Section: Study Qualitymentioning
confidence: 99%
“…One study was not in English, Dutch or German. 19 These seven studies were excluded; hence, 15 publications remained for critical appraisal [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] (Table 1).…”
Section: Search and Selectionmentioning
confidence: 99%